PROYEK LINTAS JENJANG SEBAGAI STRATEGI UNTUK MENINGKATKAN SIKAP DAN MOTIVASI BELAJAR IPA BAGI SISWA DISABILITAS: - - Mirwa Adiprahara Anggarani; Aris Rudi Purnomo; Erlix Rakhmad Purnama; Dinda Herli Septiana; M. Nasir Nasir (Universitas Negeri Surabaya, 2026)
Putra Harapan Special Needs School in Waru, Sidoarjo, is a special needs school that provides education for students with disabilities or exceptional intelligence, either inclusively (joining a regular school) or as a special education unit. Several obstacles exist in the implementation of education, particularly in the teaching of science subjects. The physical, emotional, mental, or social limitations of students with special needs, coupled with the supporting infrastructure, often cannot optimally support science learning. These problems result in low attitudes and motivation to learn science among students with disabilities. The goal of the PKM program is to explore cross-level project methods suitable for students with disabilities to improve low attitudes and motivation to learn science. This is crucial to accommodate the learning needs of students with disabilities at both the individual and school level. Furthermore, specifically related to science material, learning this material requires a longer time compared to basic skills such as measurement and observation. In other words, cross-project learning has the benefit of time efficiency without minimizing the learning experience of students with disabilities. The novelty of this project is the collaboration between students with disabilities at different levels when completing science projects. Furthermore, the learning process, connected to the UDL concept, is an example of disability-friendly learning while still teaching critical thinking and problem-solving skills. The topic chosen in this cross-level science learning project is “My Telang My Expression”, where at the elementary school level, students are taught to recognize the parts of the telang tree, at the junior high school level, students are taught to cultivate telang and at the senior high school level, students are taught to make ecoprint bags from telang flowers. Through this program, there has been an increase in the quality of science learning which is reflected in the increase in attitudes and motivation to learn science thus improving science learning outcomes. In addition, there has been an increase in student learning outcomes at each level and an increase in teacher creativity in presenting learning materials. In this Abdimas Research scheme, a number of data will be produced as a representation of the program, which is also the research data that underlies the production of this cross-level project method.